Evaluation of Drug Use in Gastroesophageal Reflux Disease (GERD) Patient at the Outpatient Installation - Wardaniati, Isna; Zuliana, Donita (Poltekkes Kemenkes Riau, 2024)
Gastroesophageal Reflux Disease (GERD) is a disorder in which stomach contents reflux repeatedly into the esophagus, causing disturbing symptoms or complications. Heartburn and regurgitation are the hallmark symptoms of GERD. This study aims to determine the evaluation of drug use which includes the right indication, the right dose, the right drug and the right interval. The subjects in this study were GERD patients who met the inclusion criteria and were determined based on the slovin formula. The research method used is observational with a cross-sectional approach with a purposive sampling technique where this study describes and examines drug use in GERD patients at Aulia Hospital Pekanbaru in 2022. The results show drug use in GERD patients at the Outpatient Installation at Aulia Hospital Pekanbaru namely 100% right indication, 100% right dose, 100% right drug, and 100% right interval.